2017
DOI: 10.1051/matecconf/201713302006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shock absorber temperature on vehicle ride comfort and road holding

Abstract: Abstract. In this work shock absorber damping characteristics at different temperature conditions are determined. The variation of damping properties of the shock absorber depending on the temperature is given. An assessment of ride comfort and road holding characteristics for different temperatures is made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In previous scientific research, shock absorber tests results could be found that take into account temperature [5,10,14,18] and their impact on the driving comfort of the user [13]. Studies of the shock absorbers filled with numerous types of fluids were also presented in [12], where the authors presented their heating characteristics during operation with a constant amplitude and frequency.…”
Section: Highlights Abstractmentioning
confidence: 99%
“…In previous scientific research, shock absorber tests results could be found that take into account temperature [5,10,14,18] and their impact on the driving comfort of the user [13]. Studies of the shock absorbers filled with numerous types of fluids were also presented in [12], where the authors presented their heating characteristics during operation with a constant amplitude and frequency.…”
Section: Highlights Abstractmentioning
confidence: 99%
“…The interaction between the tyre and the road surface is a source of vibrations. These vibrations affect the ride and the vibro-acoustic comfort as well as the road holding [1,2]. They depend on the tyre characteristics, which are similar to those of air-springs [3] for frequencies below 30 Hz.…”
Section: Overview Of the Problem And Setting The Aimmentioning
confidence: 99%
“…Indicative of the performance of the shock absorber are its operating diagrams. They are obtained on hydraulic and electrodynamic stands equipped with the necessary transducers of force, displacement and velocity [11][12][13].…”
Section: Introductionmentioning
confidence: 99%